1996
DOI: 10.1093/oxfordjournals.aje.a008695
|View full text |Cite
|
Sign up to set email alerts
|

Case Series Analysis of Adverse Reactions to Vaccines: A Comparative Evaluation

Abstract: A modified cohort method has been proposed for estimating the relative incidence of rare adverse reactions after vaccination. The method requires only a sample of the cases, thus avoiding the need for following large population cohorts or selecting controls. This case series method has statistical power equivalent to that of the full cohort method when the risk periods after vaccination are short and vaccine coverage is high. The method also eliminates confounding by variables associated with both the outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(165 citation statements)
references
References 0 publications
5
155
1
1
Order By: Relevance
“…This dramatically reduces confounding, because individuals serve as their own control. 17 The case-series method is therefore superior to other methodologies such as case-control or cohort studies, which are susceptible to selection bias and unmeasured confounding.…”
Section: Resultsmentioning
confidence: 99%
“…This dramatically reduces confounding, because individuals serve as their own control. 17 The case-series method is therefore superior to other methodologies such as case-control or cohort studies, which are susceptible to selection bias and unmeasured confounding.…”
Section: Resultsmentioning
confidence: 99%
“…However, no systematic evaluation of the statistical properties of the method has been undertaken. Some comparative evaluations have been done, comparing the case series method with case-control, cohort and other case only methods [1,4,6].…”
Section: Introductionmentioning
confidence: 99%
“…First, we have established that the sample size formula published by Farrington et al [4] is not accurate, as demonstrated in Tables 1 and 2. Second, we have found that a sample size formula based on the signed root likelihood ratio performs well under a wide range of scenarios, as shown in Tables 1, 2, 4 and 5.…”
Section: Discussionmentioning
confidence: 86%
“…This method was described by Farrington et al [4]. The idea is to use ρ as the test statistic, and base the sample size formula on its asymptotic normal distribution.…”
Section: Sample Size Formula Based On the Sampling Distribution Of ρmentioning
confidence: 99%
See 1 more Smart Citation